Glucose detection in blood using near-infrared spectroscopy: significant wavelength for glucose detection - Abd. Rahim, I. M. (Penerbit UTM Press, 2016)
World Health Organization (WHO) stated in 2004, about 347 million people suffered from diabetes and from this statistic, about 3.4 million died from the complication of kidney failure, heart attack, body part amputation and adequately reported suffered from blindness. There are several non-invasive techniques in measuring the blood glucose level developed nowadays and among the popular technique is the near-infrared (NIR) measurement, ultrasonic sensor implementation, multisensory systems, absorbance of transmittance, bio-impedance, voltage intensity, and thermography. Among these techniques, there are several approaches that displayed a lot of potential, nonetheless some of them have produced unsatisfying results. The NIR technique has been applied in some of previous research, however the wavelength used vary for different researcher. There are several points of views on the significant wavelength range that contains suitable information regarding the peaks of glucose in blood. This paper is focusing on the experimental data collection using the near-infrared spectroscopy technique. This paper furthermore discussing on determine the significant peaks of glucose that is suitable to be used as the indicator of the glucose in blood. The highest significant peaks of blood glucose detected from the range around 1450nm and 1930nm.